66.0k views
5 votes
Please help asap!!!

Please help asap!!!-example-1
User Eric Fong
by
4.8k points

1 Answer

8 votes

Answer:


w = 6

Explanation:

ST = w + 6,

PR = w

From the diagram given, we can deduce that PR is the midsegment of ∆QST. Therefore, according to the midsegment theorem:

PR = ½ of ST

Plug in the values into the equation and solve for w.


w = (1)/(2)(w + 6)


w = (w)/(2) + 3 (distributive property of equality)


w - 3 = (w)/(2) (subtraction property of equality)


2(w - 3) = (w)/(2)*2 (multiplication property of equality)


2w - 6 = w


2w - 6 - 2w= w - 2w (subtraction property of equality)


- 6 = - w

Divide both sides by -1


6 = w


w = 6

User Kwah
by
5.3k points